2021
DOI: 10.3389/fspor.2021.616999
|View full text |Cite|
|
Sign up to set email alerts
|

Injury Incidence Across the Menstrual Cycle in International Footballers

Abstract: Objectives: This study aimed to assess how menstrual cycle phase and extended menstrual cycle length influence the incidence of injuries in international footballers.Methods: Over a 4-year period, injuries from England international footballers at training camps or matches were recorded, alongside self-reported information on menstrual cycle characteristics at the point of injury. Injuries in eumenorrheic players were categorized into early follicular, late follicular, or luteal phase. Frequencies were also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 45 publications
3
35
1
8
Order By: Relevance
“…It has been shown that the occurrence of musculoskeletal injuries differs according to the menstrual cycle [3][4][5][6]45,46) . Furthermore, it has been reported that the risk of ACL injury in women changes with the menstrual cycle 18,47,48) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the occurrence of musculoskeletal injuries differs according to the menstrual cycle [3][4][5][6]45,46) . Furthermore, it has been reported that the risk of ACL injury in women changes with the menstrual cycle 18,47,48) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited evidence to support their view [35,36], half of the study participants believed the hormonal changes associated with the menstrual cycle were a risk factor for injury. There is some preliminary evidence suggesting that the incidence rate and type of injuries may vary across the eumenorrheic menstrual cycle [35], and that symptoms associated with the menstrual cycle affect athletes' training and competition availability [37] but robust studies con rming the relationship between menstrual cycle phase and injury occurrence do not exist currently.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of estrogen has been suggested as a possible injury mechanism for ACLs in female athletes [122], however there is a lack of agreement regarding the influence of sex hormones on ACL injury rates. It has been reported that female soccer players had an increased incident rate during the luteal phase of the MC [123] Martin et al [124] reported that injury rates were 47% and 32% greater in the late follicular phase in comparison to the early follicular and luteal phase. However, caution is needed in the interpretation of these studies as the methodological process (small sample size), ecological validity and terminology (phase definition and confirmation) may have affected the interpretation of the original results.…”
Section: The Menstrual Cycle (Mc)mentioning
confidence: 98%